Historische Lexikographie des Deutschen Perspektiven eines Forschungsfeldes im digitalen Zeitalter - Diehl, Gerhard; Harm, Volker (Lexicographica. Series Maior, 2022)
This volume takes stock of the current state of the historical lexicography of German, sounding out the prospects for future research. It focuses on the ongoing development of dictionary projects in the digital age.